WHEN CARING IS ESSENTIAL: CURRENT OVERVIEW OF CHALLENGES IN PEDIATRIC PALLIATIVE CARE - Daemon, Anna Clara Lugato; Oliveira, Braian Bill Dias Cunha; de Almeida Pereira, Iris Elizabethe; Lopes, Laura Silva; de Carvalho, Cecília Mendes; Freitas, Isabelli Lissa Rodrigues; Campos, Kaylane Schuvartz Beraldini; de Amorim Oliveira, Renata Borba (Seven Editora, 2025)
The health of children with life-threatening illnesses encompasses the physical, social, emotional, and spiritual dimensions, and, together with the support network, is the core of pediatric palliative care (PCC). The philosophy of family-centered care is a cornerstone of successful PCC practices. Understanding the barriers that limit this practice is important to consolidate strategies that reaffirm this comprehensive care. The still-mistaken understanding of palliative care often leads to it being confused with end-of-life care. This can create difficulties for both professionals and families, due to cultural issues and the emotional challenges involved with these complex clinical conditions. The current landscape of challenges surrounding PCC primarily involves sociocultural barriers, gaps in the professional training of the multidisciplinary team involved in care, and ethical, organizational, structural, and staffing issues. In an attempt to overcome the main difficulties associated with CPP care, it is possible to point out alternatives that involve technology, instrumentalization of services, incorporation of themes such as death into our culture, ethical debates as part of daily care, and other potentialities, in light of Brazilian legislation that supports this type of care. DOI: https://doi.org/10.56238/sevened2025.029-017